Family Palliative Care Exposure and Psychological Well-Being Among Senior High School Students - Farida Nur Qomariyah; Lutfiasih Rahmawati (Health and Technology Journal (HTechJ), 2026)
Adolescents supporting family members with serious, chronic, or life-limiting illnesses face unique psychosocial challenges, yet empirical evidence from low- and middle-income countries remains scarce. This study examined the psychological well-being of senior high school students and its association with exposure to family palliative care. A cross-sectional study was conducted at a public high school in Jember from March to April 2026. Using consecutive sampling, 100 students (mean age 16.81 years, SD = 0.95; 61.0% female) were recruited from a population of 348. Psychological well-being was assessed via the validated Indonesian WHO-5 Well-Being Index, with scores below 13 indicating poor well-being. Data were analyzed using descriptive statistics, exact tests, and crude odds ratios (OR). Notably, 66.0% of respondents exhibited poor well-being overall. However, family palliative care exposure was significantly associated with WHO-5 status (p = 0.004). Counterintuitively, exposed students were nearly 4 times more likely to report adequate well-being than their unexposed peers (OR = 3.91, 95% CI = 1.62–9.41). This positive association likely reflects psychological resilience, benefit finding, and robust communal family support, rather than a direct protective effect of the illness itself. Given the multidimensional nature of family illness exposure, educational institutions must implement subtle, non-stigmatizing screening protocols and targeted referral pathways to support adolescents navigating hidden home-care responsibilities effectively.